Ecolinguistic Digital Learning (EDL): Integrating Environmental Discourse and Digital Literacy in EFL Classroom - Yudhi Pramawati, Anak Agung Istri (Journal on Studies in English Language Teaching (JOSELT), 2025)
The integration of environmental issues into English as a Foreign Language (EFL) learning has gained increasing attention in response to global sustainability challenges. At the same time, the rapid growth of social media has transformed how students access and interact with language in digital environments. This study aims to explore the implementation of the Ecolinguistic Digital Learning (EDL) model as a model-based approach to integrating environmental discourse and digital literacy in EFL classrooms. Employing a quasi-experimental design supported by qualitative data, the study involved 26 undergraduate EFL students. Data were collected through classroom observations, student reflections, interviews, and reading–writing tasks. The findings indicate that the EDL model supports meaningful language learning by encouraging critical engagement with environmental discourse, enhancing digital literacy, and fostering ecological awareness. The study highlights the pedagogical potential of EDL as an innovative model that bridges ecolinguistics, social media, and EFL instruction.